A Framework to Assess the Impact of New Animal Management Technologies on Welfare: A Case Study of Virtual Fencing - Lee, Caroline; Colditz, Ian G.; Campbell, Dana L. M. (Frontiers in Veterinary Science, 2018)
To be ethically acceptable, new husbandry technologies and livestock management systems must maintain or improve animal welfare. To achieve this goal, the design and implementation of new technologies need to harness and complement the learning abilities of animals. Here, from literature on the cognitive activation theory of stress (CATS) we develop a framework to assess welfare outcomes in terms of the animal’s affective state and its learned ability to predict and control engagement with the environment, including for instance new technologies. In CATS, animals’ perception of their situation occurs through cognitive evaluation of predictability and controllability (P/C) that influence learning and stress responses. Stress responses result when animals are not able to predict or control both positive and negative events. A case study of virtual fencing, based on avoidance learning to respond to an audio conditioned stimulus to avoid an electric shock is described. Successful learning occurs when the animal perceives cues to be predictable (audio warning always precedes a shock) and controllable (operant response to the audio cue prevents receiving the shock) and an acceptable welfare outcome ensues. However, when animals are unable to learn the association between the audio and shock cues, the situation retains low P/C leading to states of helplessness or hopelessness, with serious implications for animal welfare. New technologies or systems should ensure that predictability and controllability are at intermediate levels and that operant tasks align with learning abilities to provide optimal animal welfare outcomes.